JURIDICAL ANALYSIS OF WOMEN WHO BECOME VICTIMS OF SEXUAL HARASSMENT REVIEWED BY LAW WOMEN's PROTECTION: ANALISIS YURIDIS TERHADAP PEREMPUAN YANG MENJADI KORBAN PELECEHAN SEKSUAL DITINJAU DARI UNDANG-UNDANG PERLINDUNGAN PEREMPUAN - Kristina Baene, Eka (UPMI Proceeding Series, 2023)
In this modern era, crimes against women are rampant, one of which is sexual harassment. Sexual harassment is like a wild snowball, case after case occurs and is increasingly concerning. All the efforts of the authorities, starting from prevention efforts to sanctioning the perpetrators, instead of subsiding, the cases of harassment are getting worse in various forms. The nature of the research used is descriptive analytical which uses qualitative juridical research, using secondary data. Secondary data is obtained by means of literature study or documentation study, then all complete data and information is processed using normative analysis. Based on the results of the research, it is known that the facts of cases of harassment against women in Indonesia vary, as sexual harassment is often experienced by women who are victims. Law enforcement against victims of sexual harassment in Indonesia is by providing a portion of law enforcement that distinguishes between perpetrators of criminal acts and victims of sexual harassment. The perspective of legal protection given to victims of sexual harassment in Indonesia is that the victim has the right to be protected both before the trial is carried out, being carried out has the right to be protected both women who are victims of sexual harassment get their rights in general regulated in article 5 and article 6 of Law Number 31 of 2014 concerning amendments to Law Number 13 of 2006 concerning the protection of witnesses and victims, and victims are also entitled to receive medical assistance, rehabilitation, compensation and restitution.